(untitled) (Research, Society and Development, 2025)
This research aimed to conduct an ethnobotanical survey of plants used for medicinal purposes by a rural community in the Brazilian Northeast semiarid region. The study took place between June and October 2024 in the Euclides da Cunha-BA city, through home visits and the application of a semi-structured questionnaire. It was found that the majority of informants are woman (82%) and over 60 years old (46%). They are farmers (64%) and housewives (27%) who use medicinal plants when necessary (55%) or on a daily basis (45%). A total of 54 species were identified, distributed across 31 botanical families. The Lamiaceae family was the most representative in terms of the number of species. Of the total species used for medicinal purposes, 73% of informants indicated the use of “capim-santo” (Cymbopogon citratus) and “erva-cidreira” (Lippia alba). The medicinal flora is mainly composed of trees and shrubs (48%) and subshrubs and herbs (48%), with 30% of the species being native to Brazil. The most common diseases in the community, treated with medicinal plants, are inflammation, flu and colds, fever, headaches, and stomach pains. There is a predominance of leaf use (87%) in the preparation of teas (83%). The number of plants identified and their potential therapeutic uses reflect the rich ethnomedicinal knowledge of the rural community. The belief in the effectiveness of traditional medicine for primary healthcare will contribute to the preservation of community knowledge and help in the sustainable use of plant resources. The results of this study may contribute to phytochemical and pharmacological investigations.